Intercultural communicative competence is essential for students of international business - but can it be taught? The case of third-year BCom students - Southwood, F.; Van Heukelum, M.-L. de la Marque (South African Journal of Higher Education, 2020)
Intercultural communicative competence is essential for graduates wishing to work in the business sector. Such competence has become desirable for graduates who see themselves working in “demanding and highly-challenging international environments” (Sain, Kužnin and Roje 2017, 55‒56). In spite of the need for well-developed intercultural competence in the workplace, students of Economic and Business Science are rarely deliberately equipped with an understanding of what language, culture and communication entail. Against this background, we investigated if an intervention, in the form of a 28-lecture undergraduate course, can develop third-year BCom students’ intercultural competence so as to prepare them to deal with the heterogeneity that they will encounter in the workplace (and elsewhere), both in multilingual and multi-cultural South Africa and abroad. Based on eight of the skills and attributes identified by Deardorff (2004) as being markers of interculturally competent individuals (such as knowledge of self and others, respect, critical thinking skills, and an awareness of the importance of being interculturally competent), students (n=18) were assessed prior to the commencement of the course and again upon completion thereof. Pre- and post-course questionnaires were analysed qualitatively and quantitatively, and data were coded according to the eight Deardorff (2004) markers of intercultural competence. Additionally, a focus group discussion (n = 5) was held at the end of the course. The data showed that development took place in the students’ attitudes, knowledge and skills related to intercultural communicative competence. Certain markers of intercultural communicative competence, however, showed more substantial development than others, the notable marker showing such development being critical thinking skills. The finding is that skills indicative of intercultural competence can indeed be developed by means of a curriculum in such a way that students think more critically about (i) cultural and linguistic diversity and (ii) their responsibility as future leaders to communicate optimally in diverse cultural settings. Deliberately including courses on intercultural communication in programmes for students (not only students in Humanities and Social Sciences) could contribute to personal and professional development of students and lead to graduates who are better prepared for a career in multicultural national and international business sectors. Likewise, the introduction of in-service training in intercultural communicative competence can be considered for those who are no longer students, thereby contributing to improved intercultural communication in the workplace.